the translation takes the point A ( -1, -1) to (-1+4, 1) = (3, 1)
The refection in y = x 'flips' the points so (3, 1) becomes (1, 3) = A"
Do the same procedure for the other points to get the answer
(you should get B" = (-3, 3) )
The average of 4, 9, 16, 25 and x is 2x means that;
(4+9+16+25+x)/5=2x
Multiply both side by 5
5(54+x)/5=2x(5)
54+x=10x
Subtract x to both side
54+x-x=10x-x
54=9x
Divided 9 to both side
54/9=9x/9
x=6
Check:
Substitute x with 6
(4+9+16+25+x)/5=2x
(4+9+16+25+6)/5=2(6)
60/5=12
12=12; so x=6 which marks B as the correct answer. Have a nice day!
√(36g^6) = 6g^3 . . . . a simpler form
Well the question says "rewrite each statement using symbols so I guess it means using symbols...